2022
DOI: 10.3390/polym14163280
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Coatings of SiO2–Recycled PET Unsaturated Polyester Resin by Sol-Gel Process

Abstract: Hybrid coatings of SiO2 and recycled unsaturated polyester resin (R-UPR) from recycled polyethylene-terephthalate (PET) were prepared by the sol-gel process on glass substrates. First, SiO2 was synthesized by the sol-gel process using a tetraethyl orthosilicate (TEOS) solution. Next, bis(2-hydroxypropyl-terephthalate) (BHPT) was synthesized from mechanical and chemical recycling (glycolysis) of post-consumer PET bottles in propylene glycol (PG) using ZnA as catalyst, in a Vessel-type reactor (20–200 °C); malei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…It is shown that at the angle of attack of the hydroabrasive å = 45°, the wear resistance coefficient of the matrix is K = 1.32. The authors [ 11 , 24 , 52 , 53 , 54 ] proved that the intensity of wear depends on various destruction processes: knocking out the coating surface with an abrasive mixture and its deformation. At the same time, the dominant influence of each of the processes depends on the cohesive strength of the CM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is shown that at the angle of attack of the hydroabrasive å = 45°, the wear resistance coefficient of the matrix is K = 1.32. The authors [ 11 , 24 , 52 , 53 , 54 ] proved that the intensity of wear depends on various destruction processes: knocking out the coating surface with an abrasive mixture and its deformation. At the same time, the dominant influence of each of the processes depends on the cohesive strength of the CM.…”
Section: Resultsmentioning
confidence: 99%
“…To improve the properties of polymers, including those based on epoxy, plasticizers and fillers are introduced into the oligomer [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. It should be noted that the introduction of modifiers is promising, since such additives with a small content (1–5%) allow a significant increase in the indicators of adhesive and cohesive strength of epoxy composites [ 10 , 13 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. The latter, in turn, should be used in the form of matrices for protective coatings of working parts, including during their repair in voyage conditions of sea and river transport vessels.…”
Section: Introductionmentioning
confidence: 99%
“…Observing the infrared spectra of the aggregates in Figure 4b, the peak at 1010 cm −1 corresponds to the antisymmetric stretching vibration of Si-O-Si, and the peaks at 771 cm −1 , 730 cm −1 , 646 cm −1 and 589 cm −1 correspond to the symmetric stretching vibration of Si-O, which are typical characteristic peaks of quartz sand [30]. In the infrared spectra of the modified aggregate, new characteristic peaks appeared at 2926 cm −1 and 2851 cm −1 , corresponding to the CH 2 and CH groups, respectively [31], indicating that the SCAs or the hydrolysate of the SCAs successfully covered the surface of the aggregate. After the modification of the aggregates, an enhancement of the Si-O-Si absorption peak at 1010 cm −1 is observed, which may be attributed to the antisymmetric stretching vibration of the newly formed Si-O-Si bonds [10].…”
Section: Ft-irmentioning
confidence: 99%
“…On the other hand, chemical recycling, particularly by glycolysis, causes the controlled degradation of PET into monomers or oligomers of lower molecular weight, known as glycolyzed products [8]. These have been used for the synthesis of a wide range of materials such as resins, coatings, and adhesives [9][10][11]. Powders obtained from post-consumer bottles PET were applied on mild steel substrates as anti-corrosive coatings [12].…”
Section: Introductionmentioning
confidence: 99%